Evaluation of Heavy Metals in Tissue of Shellfish from Can Gio Coastline in Ho Chi Minh City, Vietnam - Thi Kim Phuong, Nguyen; Cuu Khoa, Nguyen (Asian Journal of Chemistry, 2013)
This study was undertaken to determine levels of contamination of toxic metals consumed shellfish products from Can Gio coastline located in southeast of Ho Chi Minh City, Vietnam. Concentrations of As, Cd, Pb, Cr and Mn were determined in edible tissues of Mud Clam (Geloina coaxans), Clam (Meretrix lyrata), Subcrenata (Anadara subcrenata), Blood cockle (Anadara granosa), Asian green mussel (Perna viridis), White leg shrimp (Litopenaeus vannamei), Mud Crab (Scylla serrata) and Periwinkle (Litorina littorea). Sampling was carried out from March to April in 2012. Metal analysis was performed by atomic absorption spectrometry. Concentrations of As, Cd, Pb, Cr and Mn in tissue ranged from Nd-0.67, 0.04-0.64, 0.10-2.51, 0.26-0.47 and 0.75-67.41 μg g-1, respectively. The concentrations of heavy metals in all samples were lower than the permitted level set by ministry of health vietnam (MHV) and food and drug agent (FDA) except Pb in Scylla serrata. Therefore, the consumption of shellfish from Can Gio coastline might not pose a risk of metal toxicity. However, monitoring of the levels of As, Cd, Pb, Cr and Mn in water and shellfish should be carried out routinely so that appropriate prevention of contamination from these toxic metals can be implemented.